Bio-digital aesthetics as value system of post-Anthropocene architecture. (June 2020) - Pasquero, Claudia; Poletto, Marco
It is timely within the Anthropocene era, more than ever before, to search for a non-anthropocentric mode of reasoning, and consequently designing. The PhotoSynthetica Consortium, established in 2018 and including London-based ecoLogicStudio, the Urban Morphogenesis Lab (Bartlett School of Architecture, University College London) and the Synthetic Landscape Lab (University of Innsbruck, Austria), has therefore been pursuing architecture as a research-based practice, exploring the interdependence of digital and biological intelligence in design by working directly with non-human living organisms. The research focuses on the diagrammatic capacity of these organisms in the process of growing and becoming part of complex bio-digital architectures. A key remit is training architects' sensibility at recognising patterns of reasoning across disciplines, materialities and technological regimes, thus expanding the practice's repertoire of aesthetic qualities. Recent developments in evolutionary psychology demonstrate that the human sense of beauty and pleasure is part of a co-evolutionary system of mind and surrounding environment. In these terms, human senses of beauty and pleasure have evolved as selection mechanisms. Cultivating and enhancing them compensate and integrate the functions of logical thinking to gain a systemic view on the planet Earth and the dramatic changes it is currently undergoing. This article seeks to illustrate, through a series of recent research projects, how a renewed appreciation of beauty in architecture has evolved into an operational tool to design and measure its actual ecological intelligence.